2002
DOI: 10.1016/s0022-5347(05)64985-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density, Lean Body Mass and Fat Content as Measured by Dual Energy X-Ray Absorptiometry in Patients With Prostate Cancer Without Apparent Bone Metastases Given Androgen Deprivation Therapy

Abstract: Serial bone densitometry evaluation during androgen deprivation therapy may allow the detection of patients with prostate cancer at risk for osteoporotic fractures, that is those with osteopenia or osteoporosis at baseline and fast bone loss. The change in body composition may predispose patients to accidental falls, thus increasing the risk of bone fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(115 citation statements)
references
References 23 publications
4
106
0
1
Order By: Relevance
“…Studies have also shown that muscle mass and muscular strength decrease in patients treated with ADT [46], and change in muscle mass will influence muscle strength. Loss of bone density, similar to that seen in women undergoing bilateral oophorectomy, has also been reported in men who receive ADT [5,34,41]. Studies have documented up to five times the risk for osteoporotic fractures (exclusive of fractures from bone metastases) in men receiving ADT compared to healthy age-matched men [20,23,29].…”
Section: Introductionmentioning
confidence: 71%
“…Studies have also shown that muscle mass and muscular strength decrease in patients treated with ADT [46], and change in muscle mass will influence muscle strength. Loss of bone density, similar to that seen in women undergoing bilateral oophorectomy, has also been reported in men who receive ADT [5,34,41]. Studies have documented up to five times the risk for osteoporotic fractures (exclusive of fractures from bone metastases) in men receiving ADT compared to healthy age-matched men [20,23,29].…”
Section: Introductionmentioning
confidence: 71%
“…Although speculative, younger veterans may show the most pronounced impact of ADT exposure because of their relatively higher baseline lean muscle mass that will undergo a proportionately steeper decline in response to reduced testosterone when compared to older PCa survivors. Thirdly, it is important to keep in mind that previous studies have found either no net increase in overall body size in a 12 month period of exposure to ADT [33] or only small changes which ranged from 1.2% to 2.2% increases [9,32]. Thus, the net effect on weight or BMI appears to be clinically insignificant.…”
Section: Discussionmentioning
confidence: 92%
“…A review of the literature on hypogonadism noted that the condition is a strong predictor of the development of insulin resistance, central obesity, and diabetes [31]. Additionally, several previous studies have determined that men with PCa receiving ADT typically showed significantly increased fat mass and decreased lean body mass between 6 months and 1 year of treatment [8,9,[32][33][34]. In a recent prospective study, men with non-metastatic PCa and healthy controls were followed over a 2 year period [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported 0.6-4.6% annual loss in BMD for patients with non-metastatic prostate cancer. Pathological fractures caused by osteoporosis cause significant morbidity and mortality in prostate cancer patients and 21-37% of patients with prostate cancer experience pathological fractures [2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%